2011
DOI: 10.2478/v10078-011-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Overreaching During Preparation Training of Elite Tennis Professionals

Abstract: This case study evaluated the response of objective and subjective markers of overreaching to a highly demanding conditioning training mesocycle in elite tennis players to determine 1) whether players would become functionally or non-functionally overreached, and 2) to explore how coherently overreaching markers would respond.Performance, laboratory and cardiac autonomous activity markers were evaluated in three experienced male tennis professionals competing at top 30, top 100 and top 1000 level before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
(69 reference statements)
5
18
0
1
Order By: Relevance
“…However, instead of the presence of dysfunctional impaired responses in OTS, exacerbated and hastened responses were observed in ATL, compared to NCS and OTS, for both ACTH and cortisol, whereas basal levels were similar among groups. Basal cortisol and ACTH levels tended to be normal in OTS, as reported by previous studies [ 1 , 3 , 6 , 9 12 ], although some studies reported either reduced [ 23 ] or increased levels [ 34 ]; contrariwise, stimulated cortisol and ACTH levels showed predominantly reduced levels [ 1 , 3 , 7 9 ], which is corroborated by us.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, instead of the presence of dysfunctional impaired responses in OTS, exacerbated and hastened responses were observed in ATL, compared to NCS and OTS, for both ACTH and cortisol, whereas basal levels were similar among groups. Basal cortisol and ACTH levels tended to be normal in OTS, as reported by previous studies [ 1 , 3 , 6 , 9 12 ], although some studies reported either reduced [ 23 ] or increased levels [ 34 ]; contrariwise, stimulated cortisol and ACTH levels showed predominantly reduced levels [ 1 , 3 , 7 9 ], which is corroborated by us.…”
Section: Discussionsupporting
confidence: 91%
“…As summarized in Tables 1 , 2 , and 3 , basal serum hormone levels of OTS are within the normal range, and similar to ATL and to NCS, as previously observed [ 1 4 , 6 9 , 17 29 , 34 36 ].…”
Section: Resultssupporting
confidence: 85%
“…ME after OTP (↓salivary cortisol/↓salivary testosterone/↑T/C) b. Resting levels after OTP (↓salivary cortisol/nl salivary testosterone) Steinacker et al, 2000 [ 24 ] 10 Rowing PHA (CHB) - OTP (Nl total T, nl cortisol, nl DHEA-S/↓LH/↓FSH/nl aldosterone/↓insulin/↓pep C/nl prolactin/↑GH) Tanskanen et al, 2011 [ 6 ] Not Specified Multiple (military) AA (CC, CRH) nl T/C ratio/↑cortisol/↑SHBG ME (↓cortisol) Thiel et al, 2011 [ 8 ] 3 Tennis PHA (CHB) - OTP (↓IGF-1/nl T/C) Urhausen et al, 1998 [ 26 ] 17 Cycling, triathlon AA (CC, RRH) Nl Nocturnal Cathecolamines/nl GH/nl cortisol/nl insulin/nl LH/nl FSH/testosterone/nl SHBG/nl T/SHBG/nl T/C/↑ACTH ME (↓GH/↓ACTH/↓insulin/nl cortisol) Uusitalo et al, 1998 [ 28 ] 15 Middle-distance running, skiing, triathlon and orienting. PHA (CHB, RRH, CRH) - a.…”
Section: Resultsmentioning
confidence: 99%
“…This finding could be interpreted as showing that the team was coming to the end of the season and beginning to enter a phase of overtraining or that the players displayed relatively high indices of stress, aspects that were not reflected by the design of the loads or a decrease in players’ performance. Other tennis (Thiel et al, 2011) and women’s soccer (Flatt and Esco, 2015) studies that included an intense training period reported that lower HRV variables were not associated with decreased performance. Our results are similar to those of previous Yo-Yo IR1 test results, and the Yo-Yo IR1 improvement was not related to the relative changes in short-term HRV.…”
Section: Discussionmentioning
confidence: 98%
“…The use of the RESTQ-sport combined with physiological, non-invasive outcome measurements such as HRV has several precedents for monitoring the effects of the TL simultaneously with changes in stress and recovery (Dupuy et al, 2013; Morales et al, 2014; Thiel et al, 2011). Previous studies have reported similar results when comparing stress and physiological variables.…”
Section: Discussionmentioning
confidence: 99%